2020
DOI: 10.3390/ijerph17113996
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Fat Is a Negative Determinant of Bone Health in Obese Postmenopausal Women

Abstract: The protective effect of obesity on bone health has been challenged by studies that link visceral adiposity to poor bone microarchitecture in young obese men and women. In postmenopausal women, the role of visceral adipose tissue (VAT) on bone turnover markers (BTMs) has not been investigated. The aim was to investigate the impact of VAT on BTMs, total bone mineral density (BMD), vitamin D metabolites and parathyroid levels (1-84 PTH) levels in postmenopausal women. A total of 76 lean and overweight women (wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…The present data indicate that beside FMI both, subcutaneous and visceral obesity are strong predictors and critical risk factors of a low bone mass and density in older adults when controlling for the mechanical loading effects of total body weight on bone mass (see results). These results are confirmed by previous findings that identified FM 8 , 45 47 or VAT 48 50 as independent negative determinants of bone mass or bone density. The etiology of impaired bone health in obesity is multifactorial and a number of mechanistic explanations have been proposed to explain the inverse association between fat and bone (for a review see 51 ).…”
Section: Discussionsupporting
confidence: 90%
“…The present data indicate that beside FMI both, subcutaneous and visceral obesity are strong predictors and critical risk factors of a low bone mass and density in older adults when controlling for the mechanical loading effects of total body weight on bone mass (see results). These results are confirmed by previous findings that identified FM 8 , 45 47 or VAT 48 50 as independent negative determinants of bone mass or bone density. The etiology of impaired bone health in obesity is multifactorial and a number of mechanistic explanations have been proposed to explain the inverse association between fat and bone (for a review see 51 ).…”
Section: Discussionsupporting
confidence: 90%
“…After careful screening of 2803 full texts, we also excluded 2731 more studies because they evaluated the relationship between serum levels of 25(OH)D with an outcome other than anthropometric/adiposity indices, were clinical trials, animal or in vitro studies in design, editorial, and reviews, or the participants of the studies were unhealthy (with chronic diseases, such as diabetes, cancer, or chronic kidney disease). Ultimately, 72 studies ( 12 , 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , …”
Section: Resultsmentioning
confidence: 99%
“…Our systematic search identified 42 cross-sectional studies ( 12 , 13 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 79 , 83 , 84 , 85 ) and two cohort investigations ( 60 , 78 ) (with 33,815 participants) that investigated the potential relationship between 25(OH)D serum concentrations and anthropometric/adiposity indices in adults and/or elderly population. The studies about the link between 25(OH)D serum level and anthropometric indices in adults and/or elderly population were carried out in the following countries: 9 studies from USA, 3 from UK, 3 from Spain, 2 from Turkey, 4 from Saudi Arabia, 2 from Iran, 2 from India, 2 from Italy, 2 from Germany, and 18 others from China, UAE, Pakistan, Australia, Finland, England, Portugal, Malaysia, Bulgaria, Austria, Canada, Denmark, Greece, New Zealand, and the Netherlands.…”
Section: Resultsmentioning
confidence: 99%
“…Women in menopause have a rapid increase in bone turnover due to a rapid decrease in estrogen levels, which causes higher bone resorption and negative bone balance, leading to bone loss. Despite most studies having confirmed a negative association between VFA and OC and β-CTX in postmenopausal women ( 20 , 32 ), fewer studies have explained the underlying relationships between perirenal fat and BTMs. A recent study that enrolled 234 T2DM patients reported that PrFT measured by ultrasound is negatively correlated with β-CTX ( 33 ).…”
Section: Discussionmentioning
confidence: 99%